2003
DOI: 10.1038/sj.ejcn.1601743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in Greek school-aged children and adolescents

Abstract: The aim of the present study, which was part of the Health Behavior in School Aged Children (HBSC) study, was to provide national estimates for overweight and obesity in Greek school-aged children and adolescents. A nationwide multistage procedure was followed to obtain a representative sample of children and adolescents aged 11.5, 13.5 and 15.5 y. The resultant sample consisted of 4299 students, 51.3% girls and 48.7% boys. Self-reported weight and height data were used. According to the body mass index cutoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
5
11

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 17 publications
8
30
5
11
Order By: Relevance
“…Compared with the results reported by Karayiannis et al (2003), similar values were found for the prevalence of overweight and obesity in boys but higher values were reported for girls in the present study. This discrepancy might be attributed, in part, to the fact that body weight and height were self-reported in the study of Karayiannis et al (2003).…”
Section: Discussioncontrasting
confidence: 33%
See 1 more Smart Citation
“…Compared with the results reported by Karayiannis et al (2003), similar values were found for the prevalence of overweight and obesity in boys but higher values were reported for girls in the present study. This discrepancy might be attributed, in part, to the fact that body weight and height were self-reported in the study of Karayiannis et al (2003).…”
Section: Discussioncontrasting
confidence: 33%
“…To the best of our knowledge, only one study has examined the prevalence of overweight and obesity in Greek children and adolescents in a national representative sample (Karayiannis et al, 2003). In that study, however, body weight and height were self-reported.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, if compared, the prevalences of overweight and obesity obtained applying the IOTF and the WHO's cutoff points of BMI-for-age will yield similar results . Although the use of the IOTF reference may slightly overestimate overweight and underestimate the prevalence of obesity, the differences were not statistically significant, for example, in a Greek sample (Karayiannis et al, 2003). Furthermore, the IOTF reference (Cole et al, 2000) has been suggested to be appropriate for the identification of overweight and obesity since the proposed cutoffs are a result of Overweight in Bolivian adolescents A Pérez-Cueto et al the analysis of international pooled data and therefore constitute the best instrument available to date for epidemiological studies (Woodruff and Duffield, 2002;.…”
Section: Discussionmentioning
confidence: 78%
“…Self-reported weight and height data were used for the calculation of body mass index (BMI) and the assessment of overweight and obesity according to the International Obesity Task Force (IOTF) cutoff points (Cole et al, 2000). These results are presented elsewhere (Karayiannis et al, 2003).…”
Section: Hbsc Questionnairementioning
confidence: 99%